Polarized signatures of adiabatically expanding hotspots in Sgr A*'s accretion flow. Issue 2 (27th January 2023) - Michail, Joseph M; Yusef-Zadeh, Farhad; Wardle, Mark; Kunneriath, Devaky
ABSTRACT: We report 235 GHz linear and circular polarization (LP and CP) detections of Sgr A* at levels of 10 per cent and -1 per cent, respectively, using ALMA. We describe the first full-Stokes modelling of an observed submillimetre flare with an adiabatically expanding synchrotron hotspot using a polarized radiative transfer prescription. Augmented with a simple full-Stokes model for the quiescent emission, we jointly characterize properties of both the quiescent and variable components by simultaneously fitting all four Stokes parameter light curves. The hotspot has magnetic field strength 71 G, radius 0.75 Schwarzschild radii, and expands at speed 0.013c assuming magnetic equipartition. The magnetic field's position angle projected in the plane-of-sky is ≈55° East of North, which previous analyses reveal as the accretion flow's angular momentum axis and further supports Sgr A* hosting a magnetically arrested disc. The magnetic field is oriented approximately perpendicular to the line of sight, which suggests repolarization as the cause of the high circular-to-linear polarization ratio observed at radio frequencies. We additionally recover several properties of the quiescent emission, consistent with previous analyses of the accretion flow, such as a rotation measure ≈−4.22 × 10 5 rad m −2 . Our findings provide critical constraints for interpreting and mitigating the polarized variable emission in future Event Horizon Telescope images of Sgr A*.